PROBLEMS OF IMPROVING THE STANDARDS OF THE CRIMINAL CODE ON THE RESPONSIBILITY FOR THE PROVOCATION OF COMMERCIAL BRIBERY OR CORRUPTION OFFENSE (ART. 349 OF THE CRIMINAL CODE) - Rakhmetov, Саттар Муканович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
The article analyzes the provisions of the Criminal Code of the Republic of Kazakhstan on the responsibility for the provocation of commercial bribery or corruption. The drawbacks wording of Art. 349 of the Criminal Code and discusses ways to improve the wording of this article.